The Effectiveness of the Educational Loss Program in Developing Conceptual Comprehension in Science in Public Schools in Ajloun Governorate from The Point of View of school Principals - AbuEnab, Yasmeen AbdUllah Suliman (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the effectiveness of the educational loss program in developing conceptual comprehension in science For Grades (fifth, sixth, and seventh) in public schools in Ajloun Governorate from the school principals point of view. To achieve the objectives of the study, the researcher used the descriptive survey method, and a questionnaire consisting of (24) items divided into three areas, which were distributed to a random sample consisting of (110) female and male school principals.The result of SPSS analysis shown that The effectiveness of the educational loss program in developing conceptual comprehension in science in public schools in Ajloun Governorate from school principals perspective was High with average (3.71 out of 5) , The finding also showed there is no statistically significant differences at (α≤0.05) refers to principals sex (male and female) in addition there were statistically significant differences refers to principals years of experience in favor of (10 years and more).